Image analysis and health of Moringa oleifera seeds - Vasconcelos, Michelle Conceição; Costa, Joel Conceição; Silva-Mann, Renata; Oliveira, Andréa dos Santos; Bárbara, Claudio das Neves Vieira; Carvalho, Maria Laene Moreira de (Comunicata Scientiae, 2019)
Moringa oleifera Lam. (moringa) is a tree species with the potential for use in biofuel production. However, knowledge regarding the morphology and physiology of its seeds is needed to establish field production. The goals of the present study were to investigate the internal morphology of seeds by X-ray and to identify the fungal microorganisms present in the seeds. Two hundred seeds from two trees were analyzed. The morphological characterization of the seeds was performed using an X-ray chamber with an X-ray source operated at 22 kV for 14.8 s. The fungi were identified using the blotter test. The seeds were characterized as (a) full and well formed, (b) with internal space and poorly formed and (c) stained or damaged. The malformed seeds with an internal space showed the highest incidence (55%). The results indicated that X-ray tests are valid for the internal characterization of moringa seed morphology. The fungi Aspergillus niger, Aspergillus flavus, Alternaria sp., Fusarium sp., Penicillium sp. and Phomopsis sp. occurred in moringa seeds.